Relationship analysis between HRM practices and core competencies: Field research on a sample of workers in the Ministry of Construction and Housing, Municipalities and Public Works - جثير, سعدون حمود; جهاد, عدي صلاح (Journal of Economics and Administrative Sciences, 2025)
The main objective of the research is to analyze the correlation betweenhuman resource management practices and the basic capabilities. The researchwas carried out in the practical part of the Ministry of Construction, Housing,Municipalities and Public Works. Human Resources are the most importantresources owned by the Organization. And other resources, but they cannot usethem efficiently and effectively without the presence of human resources withrare, unique and unmatched natural resources by competitors, the organizationis able to guide and exploit The focus on the core competencies of the futureincludes the ability and the ability to defend and attack at the same time to dealwith the changing environment as a characteristic of the age. In particular, theconsequences of this environmental change require an assessment. Theimprovement or enhancement of the core competencies, which leads to meet therequirements of the beneficiaries of the services provided by the Ministry ofConstruction, Housing, Municipalities and Public Works. In this framework, theresearch sample included the employees of the Ministry (132) The questionnairehas been used as a data collection tool, and the research has found a correlationbetween human resources management practices and core competencies.